Engineering and Technology Transfer of a Multi-Stage Filtration System to Provide Safe Drinking Water for Hydro-Meteorological Disaster-Affected Communities in Bireuen - Rahmat Fadhil; Raida Agustina; Hendra Halim (Jurnal Pengabdian Bakti Akademisi, 2026)
This community service program addressed post–hydro-meteorological disaster disruptions to safe water access in Rancong Village, Kuta Blang Subdistrict, Bireuen Regency, Aceh, where flooding and environmental contamination increased the risk of unsafe household water and hindered recovery of daily activities. The program aimed to restore access to safer drinking water and strengthen community capacity to operate and maintain the service through an integrated, appropriate-technology intervention. The implementation combined participatory action cycles with community co-design, student service-learning through an impact-oriented field program, and an asset-based approach to leverage local resources for sustainability. Activities were conducted in sequential stages: stakeholder coordination and joint decision-making, rapid needs and risk assessment of water sources, engineering design and installation of an integrated multi-stage emergency drinking water filtration unit, field functionality and performance testing using a before–after measurement approach, technology transfer through hands-on training, and development of standard operating procedures and an operation-and-maintenance logbook managed by the village team. The program produced key outputs: a validated baseline of local water risks and service needs; an installed filtration unit at a community-agreed location; community training and operational guidelines to ensure consistent daily use; and an agreed operation-and-maintenance mechanism to support continuity beyond the project period. Overall, the program demonstrated that pairing emergency water treatment technology with structured community governance and practical capacity building can accelerate post-disaster recovery of basic services and provide a replicable model for similar villages affected by flooding and related hazards.